Spall strength and fracture behavior of Ti–10V–2Fe–3Al alloy during one-dimensional shock loading. (January 2018) - Ren, Yu; Xue, Zhiyong; Yu, Xiaodong; Tan, Chengwen; Wang, Fuchi; Cai, Hongnian
Highlights: The SIM transition has a harmful effect on the spallation resistance of Ti-alloy. Ti–10V–2Fe–3Al (Ti–1023) is likely to spall in a mixed fracture manner. The spall strength of Ti–1023 drops by ∼20% as the shock stress exceeds 9 GPa. SIM phase promotes the nucleation and propagation of micro-damages in Ti–1023. Abstract: The spall fracture behavior of a typical metastable β titanium alloy, Ti–10V–2Fe–3Al, is systemically investigated during one-dimensional shock loading. Shock pressures over 14 GPa are achieved through a series of plate impact experiments. The results show that the shock-induced β-to-α″ martensite (SIM) phase transformation strongly influences the spall fracture behavior of this alloy. The spall strength of Ti–10V–2Fe–3Al ranges from 2.5 to 3.1 GPa, and drops by nearly 20% as the shock pressure exceeds 9 GPa. The acicular SIM phases provide additional nucleation sites and propagation paths for micro-damage, leading to the reduction of spall strength of Ti–10V–2Fe–3Al. Microstructural analyses also suggest that Ti–10V–2Fe–3Al is likely to spall in a mixed fracture manner containing both brittle and ductile failure features. The spall fracture surface of this alloy is very rough and consists of facets covered by ductile dimples.